Penile Mondor’s Disease: Primum Non Nocere!* - Polat, Haci; Yucel, Mehmet Ozgur; Gok, Alper; Benlioglu, Can; Cift, Ali; Sarica, Mehmet Akif (Urology Journal, 2015)
Purpose: Penile Mondor’s disease (superficial thrombophlebitis of the dorsal vein of the penis) is a rare clinical diagnosis. It is an easily diagnosed and treated disease. Nevertheless, when reviewing the literature, we considered that unnecessary tests are carried out for diagnosis. In this study, we aimed to indicate the redundancy of Doppler ultrasonography for diagnosis of penile Mondor’s disease. Materials and Methods: Seven patients with the clinical presentation of penile Mondor’s disease were included in the study. In the first two patients, penile Doppler ultrasonography was performed for diagnostic purposes by applying a vasoactive intracavernosal agent. This diagnostic procedure was not implemented in the next five patients. Results: Physical examinations revealed cord-like thickening lesions on dorsal and dorsolateral penis. In the first two patients, who penile Doppler ultrasonography with an intracavernosal vasoactive agent was used for diagnostic purposes, was developed priapism. We did not use penile Doppler for more patients as this would be unethical according to us. Conclusion: Recovery from penile Mondor’s disease is usually spontaneous and smooth. A simple physical examination is sufficient for diagnosis, and palliative treatment is effective. For the diagnosis of this disease, unnecessary tests should be avoided so that patients are not harmed.